Assessing the profesional competence of physical education teachers in Bengkulu Province: Examining the role of teacher characteristics - Syafrial; Nopiyanto, Yahya Eko; Pujianto, Dian; Insanistyo, Bayu; Cotton, Wayne (Journal Sport Area, 2023)
The success of the physical education learning process is determined by the teachers’ professional competence. Therefore, the purpose of this study is to evaluate the level of professional competence of physical education teachers in Bengkulu Province, with the main objective being to describe and determine the level of professional competence of teachers and the differences based on several variables, namely gender, teaching location, and teaching experience. A quantitative descriptive method was implemented in this study to achieve the research objectives. The research sample was 49 physical education teachers in Bengkulu Province. Techniques and instruments for collecting research data were in the form of receipts which were distributed via GoogleForm. An Independent sample t-test was used to analyze data regarding differences in the professional competence of physical education teachers based on gender. Meanwhile, one-way ANOVA was used to analyze differences in the professional competence of physical education teachers based on teaching location and teaching experience. The results of this study indicated that physical education teachers in Bengkulu Province have a very high level of professional competence, and there were no differences in teachers' professional competence based on gender, teaching location, or teaching experience. The limitations of this research included the involvement of a relatively small number of samples, the restriction of samples to public schools, and a lack of diversity in the sample variations. For further research, it is advisable to involve a larger number of samples from private schools and islamic schools. It was also recommended that physical education teachers develop competence in conducting classroom action research.